Structural determinants of oxidative folding in proteins - Welker, Ervin (The National Academy of Sciences, 2001)
A method for determining the kinetic fate of structured disulfide species (i.e., whether they are preferentially oxidized or reshuffle back to an unstructured disulfide species) is introduced. The method relies on the sensitivity of unstructured disulfide species to low concentrations of reducing agents. Because a structured des species that preferentially reshuffles generally first rearranges to an unstructured species, a small concentration of reduced DTT (e.g., 260 μM) suffices to distinguish on-pathway intermediates from dead-end species. We apply this method to the oxidative folding of bovine pancreatic ribonuclease A (RNase A) and show that des[40–95] and des[65–72] are productive intermediates, whereas des[26–84] and des[58–110] are metastable dead-end species that preferentially reshuffle. The key factor in determining the kinetic fate of these des species is the relative accessibility of both their thiol groups and disulfide bonds. Productive intermediates tend to be disulfide-secure, meaning that their structural fluctuations preferentially expose their thiol groups, while keeping their disulfide bonds buried. By contrast, dead-end species tend to be disulfide-insecure, in that their structural fluctuations expose their disulfide bonds in concert with their thiol groups. This distinction leads to four generic types of oxidative folding pathways. We combine these results with those of earlier studies to suggest a general three-stage model of oxidative folding of RNase A and other single-domain proteins with multiple disulfide bonds.